PENGARUH SELF-EFFICACY TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Lusia Oktaviana Ule; Natalia Peni; Konstantinus Denny Pareira Meke (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This research aims to determine the effect of self-efficacy on the learning outcomes of grade VIII mathematics students of State Junior High School. This type of research is ex post facto, using a quantitative approach. The population in this study was grade VIII students of SMP Negeri 1 Ndona. The sample in this study was 24 grade VIII B students. The instrument used is a questionnaire. Technical data analysis uses simple regression analysis. Based on the tests conducted, it show a significant influence between self-efficacy and the learning outcomes of grade VIII mathematics students at SMP Negeri 1 Ndona. The conclusion of this study is that there is a significant influence of self-efficacy on students' mathematics learning outcomes. It shows that 61.2% of learning outcomes are influenced by self-efficacy, while 38.8% are influenced by other factors not discussed in this study.